Pengaruh Harga dan Promo terhadap Loyalitas Konsumen Shopeefood di Indonesia - Hamzah, Salshabilla Adinda; Hasanah, Yulia Nur (Jurnal Ilmu Manajemen, 2023)
Online Food Delivery services have now become something that is needed by the people of Indonesia, so that OFD services are now competing for consumers. In this study aims to determine the effect of price and promotion on consumer loyalty Shopeefood.The method used in this study is to use quantitative methods and use the Likert scale as a measurement scale and data analysis using multiple linear regression. In this study using nonprobability sampling techniques, purposive sampling and calculations using the Bernoulli formula, then distributing questionnaires to 385 respondents and processing data using SPSS.The results of this study indicate that there is a significant influence between price and consumer loyalty at Shopeefood at 5,311 and there is a significant influence between promotion and consumer loyalty at Shopeefood at 8,225. Then prices and promotions simultaneously have a significant effect on consumer loyalty at Shopeefood 123,763. The contribution of the influence of the independent variable price and promotion on the dependent variable of consumer loyalty is 39.3% while the remaining 60.7% is the contribution of the influence of other variables outside this study.